The influence of corporate governance on bank risk during a financial crisis - Felício, J. Augusto (2022)
Using agency theory, we explore the relationship between corporate governance mechanisms and bank risk. We employ panel data analysis to study the 97 largest European listed banks between 2006 and 2010, thereby covering the most recent international financial crisis. The results show that corporate governance mechanisms influence bank risk. During the financial crisis, different governance mechanisms can minimise or accentuate the agency conflict between shareholders and managers. In our model, bank size and G.D.P. per capita also exert a considerable influence.